Impacts of rapid mass vaccination against SARS-CoV2 in an early variant of concern hotspot - Jörg Paetzold; Janine Kimpel; Katie Bates; Michael Hummer; Florian Krammer; Dorothee von Laer; Hannes Winner (Nature Communications, 2022)
Schwaz, Austria, experienced SARS-CoV-2 outbreaks caused by variants of concern in early 2021 and conducted a mass vaccination campaign in response, with 70% of the adult population vaccinated after 5 days. Here, the authors show that this campaign resulted in reduced infections and hospitalisations.